Effect of Plant Media Composition and POC Doses of Rabbit Urine on Growth and Yield of Melon (Cucumis melo L.) Plants - Gita Ayu Lestari; Sumarsono; Eny uskhah Fuskhah (Jurnal Pertanian Tropik, 2019)
Melon has a high economic value but in its cultivation, this plant requires quite an intensive handling.One effort to increase the production of melon plants is modifying planting media composition andfertilizing. This research aimed to examine the interaction between plant media composition and therabbit urine fertilizer dosage on melon growth and yield. The research was held on April 4 to August4, 2019, at The Agro Fruit Purwosari Greenhouse, Mijen, Semarang and Ecology, and CropProduction Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University,Semarang. The study used a completely randomized factorial design 3x5 with 5 replications. The firstfactor was the growing media composition of 100% husk charcoal (M1), 75% husk charcoal + 25%soil (M2), 50% husk charcoal + 50% soil (M3). The second factor was rabbit urine fertilizer dosageof 55 ml/plant (P1), 82,5 ml/plant (P2), 110 ml/plant (P3), 137,5 ml/plant (P4), 165 ml/plant (P5).Data were analyzed by variance and proceeded with the DMRT test. The observed variables wereplant height, amount of leaves, harvest age, fruit weight, fruit diameter, fruit sweetness level, crown,and root fresh weight, crown and root dry weight. The results of the study showed that the interactionof the growing media composition and rabbit urine fertilizer dosage was significant (P<0.05) on theparameters of plant height, amount of leaves, and fruit sweetness level. The treatment of (M2)obtained the highest result on the parameters of plant height, amount of leaves, and fruit sweetnesslevel but had not been shown on the parameters of harvest age, fruit weight, fruit diameter, crownand root fresh weight, crown, and root dry weight.